Respuesta :
Answer: [tex]=528[/tex]
Step-by-step explanation:
You have this expression:
[tex]2(3x^3 + 2y^2)[/tex]
You already know that the value of the variable "x" is:
[tex]x=-2[/tex]
And the value of the variable "y" is:
[tex]y=12[/tex]
Therefore, you can substitute the value of the variable "x" and the value of the variable "y" into the expression.
Then you get:
[tex]2(3(-2)^3 + 2(12)^2)=2(-24+288)=2(264)=528[/tex]
Answer:
528
Step-by-step explanation:
2(3х³ + 2у²)
Where x = -2 and y = 12 which means whenever you sees x, put -2 in replacement and y put 12
So we solve;
2(3x³ + 2y²), x = -2, y = 12
2[3(-2)³ + 2(12)²]
2[3(-8) + 2(144)]
2[-24 + 288]
open the bracket by multiplying by 2
-48 + 576
combine
528